Fungos melanizados associados a formigas cortadeiras (Formicidae: Tribo Attini) - Guedes, Fábio Lúcio Antunes [UNESP] (2010)
Leafcutter ants are considered pests in agriculture for their impact in human crops, as they behave utilizing foliar fragments to raise their simbiont fungi (Agaricales: Lepiotaceae) inside their nest. Recent studies have noticed that other fungi may be associated to ants inside their nests, for instance, fungi with melanized wall, known by “dematiaceous”. Historically, many black fungi have been noticed as fitopathogens of many plant cultures with economic importance, highlighting dematiaceous ecological behavior importance in this study. This investigation had the purpose of amplifying ecological knowledge of this fungi, isolating and identificating dematiaceous fungi found in Attini nests, having the intention of understanding plant pathogens dispersion by ants. In this work, 66 isolates were characterized in the following genus: Aspergillus, Penicillium, Paecilomyces, Oxyporus, Rhodotorula, Bipolaris, Curvularia, Fusarium, Giberella, Paraphaeosphaeria, and Cladosporium. The genus Bipolaris, Curvularia, Fusarium and Giberella are known for their opportunistic behaviour, with some published human infections in literature. Fusarium is a notorious fitopathogen, with wide number of descriptions and studies involving pathogenicity development, biochemistry and genetics. The isolates outline is of phyto – associated (phytopathogens, endophytic or epiphitic), fulfilling this work intention in alarming fungi capacity of dispersal by ants. The comprehension of phytopathogenical processes may be clarified based on the knowledge of oportunistics fungi that may utilize ants bodies for their own dispersal. The identification of isolates with capacity of infecting humans brings out public health issues.